Social interaction, languaging and the operational conditions for the emergence of observing - Raimondi, Vincenzo (Frontiers in Psychology, 2014)
In order to adequately understand the foundations of human social interaction, we need to provide an explanation of our specific mode of living based on linguistic activity and the cultural practices with which it is interwoven. To this end, we need to make explicit the constitutive conditions for the emergence of the phenomena which relate to language and joint activity starting from their operational-relational matrix. The approach presented here challenges the inadequacy of mentalist models to explain the relation between language and interaction. Recent empirical studies concerning joint attention and language acquisition have led scholars such as Tomasello and his colleagues to postulate the existence of a universal human “sociocognitive infrastructure” that drives joint social activities and is biologically inherited. This infrastructure would include the skill of precocious intention-reading, and is meant to explain human linguistic development and cultural learning. However, the cognitivist and functionalist assumptions on which this model relies have resulted in controversial hypotheses (i.e., intention-reading as the ontogenetic precursor of language) which take a contentious conception of mind and language for granted. By challenging this model, I will show that we should instead turn ourselves towards a constitutive explanation of language within a “bio-logical” understanding of interactivity. This is possible only by abandoning the cognitivist conception of organism and traditional views of language. An epistemological shift must therefore be proposed, based on embodied, enactive and distributed approaches, and on Maturana’s work in particular. The notions of languaging and observing that will be discussed in this article will allow for a bio-logically grounded, theoretically parsimonious alternative to mentalist and spectatorial approaches, and will guide us towards a wider understanding of our sociocultural mode of living.